The Role of Ontology in Marketing Management Decisions in Manufacturing Companies: A Scoping Review - Sunyoto, Agus Bambang; Winarno, Agung (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
As a manager, it is necessary to have curiosity and knowledge in determining a decision. Managers can integrate ontology as their framework to determine their marketing strategy. Managers analyze current market demand or trends or see “what” and “how” a situation occurs that can be developed into a strategy. The purpose of this scoping review is to map how marketing managers apply ontology in making their decisions. The article survey resulted in 5 articles that fit the research objectives. This research aims to determine the role of ontology in determining marketing management decisions. From the four articles, it was found that managers' decisions do not consider emotions but rational data and managers must have a marketing strategy that is in accordance with the achievement of organizational goals. This research can be used by marketing managers to consider creating a framework with an ontological foundation to decide marketing strategies in their organizations and further research references related to ontology in management decisions, especially marketing management.